Multimodal mother–offspring recognition: the relative importance of sensory cues in a colonial mammal. (December 2018) - Wierucka, Kaja; Pitcher, Benjamin J.; Harcourt, Robert; Charrier, Isabelle
Abstract : Animals often employ multiple sensory modalities for communication and recognition; however, the combination of sensory cues used by individuals in given contexts will vary. Although mother–offspring recognition has been widely investigated and is known to be a multimodal process in gregarious mammal species, there is a dearth of information about the interactions between various sensory cues. Here we show how acoustic, olfactory and visual cues are used in a synergistic way in Australian sea lion, Neophoca cinerea, mother–offspring recognition. We interpret the results using a cost–benefit perspective to disentangle the evolutionary pressures on each component of this communication system. Although olfactory cues can convey individual identity information it was their presence, not their congruency, that prompted female sniffs. We found that calls needed to be from the female's own pup for the identification process to be successful, with the information encoded in acoustic cues overriding that of olfactory cues. Despite each sensory cue accurately conveying identity information when presented in isolation, in a multimodal setting their importance, function or role may change and seems to be driven by the costs and benefits of obtaining information resulting from the constraints imposed by the active space of cues. Highlights: Sea lion mothers use multiple senses for pup recognition. Individually, acoustic and olfactory cues convey accurate identity information. Acoustic, olfactory and visual cues act synergistically in mother-pup recognition. When multiple cues are present their relative importance and function change. All information encoded in olfactory cues is not used when acoustic cue is present.